2011
DOI: 10.1016/b978-0-444-53839-0.00003-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cytokines in slow wave sleep

Abstract: Cytokines such as tumor necrosis factor alpha (TNFα) and interleukin-1 beta (IL1β) play a role in sleep regulation in health and disease. TNFα or IL1β injection enhances non-rapid eye movement sleep. Inhibition of TNFα or IL1β reduces spontaneous sleep. Mice lacking TNFα or IL1β receptors sleep less. In normal humans and in multiple disease states, plasma levels of TNFα covary with EEG slow wave activity (SWA) and sleep propensity. Many of the symptoms induced by sleep loss, for example, sleepiness, fatigue, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 47 publications
1
82
1
Order By: Relevance
“…There are several established mechanisms through which the peripheral immune system can influence the brain and subsequent behavior, including via the direct transport of cytokines into the brain or communication of immune status to the brain via the vagus nerve (Wilson et al, 2002;Kelley et al, 2003;Ahles and Saykin, 2007). Many proinflammatory cytokines increase sleep and lethargy following peripheral immune activation (Krueger et al, 2001(Krueger et al, , 2011Opp, 2005). Previous studies have demonstrated that mice receiving doxorubicin, cyclophosphamide, and 5-fluorouracil have increased central inflammation and display a 'fatigue' phenotype (reduced voluntary wheel running behavior) that progressively worsens with each chemotherapy treatment Smith et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are several established mechanisms through which the peripheral immune system can influence the brain and subsequent behavior, including via the direct transport of cytokines into the brain or communication of immune status to the brain via the vagus nerve (Wilson et al, 2002;Kelley et al, 2003;Ahles and Saykin, 2007). Many proinflammatory cytokines increase sleep and lethargy following peripheral immune activation (Krueger et al, 2001(Krueger et al, , 2011Opp, 2005). Previous studies have demonstrated that mice receiving doxorubicin, cyclophosphamide, and 5-fluorouracil have increased central inflammation and display a 'fatigue' phenotype (reduced voluntary wheel running behavior) that progressively worsens with each chemotherapy treatment Smith et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, TNF promotes non-rapid eye movement sleep (NREMS) after central or peripheral administration (Imeri and Opp, 2009; Kapas et al, 1992; Krueger et al, 2011; Zielinski et al, 2013), TNF mRNA and protein are highest during sleep (Bredow et al, 1997; Floyd and Krueger, 1997), and mice lacking the TNF p55 receptor spend less time NREMS (Feng et al, 1997). To reach its CNS receptors, blood-borne TNF must cross the blood–brain barrier (BBB) and it does so by a saturable transport system (Gutierrez et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have demonstrated the existence of reliable brain-specific markers of sleep homeostasis, such as Homer1a (9, 37-40), but also extremely robust cytokine markers with known functional roles, such as IL-1 and TNF, which show increased levels in response to sleep loss (41,42). As expected, expression of HOMER1 in blood did not show a significant effect of sleep restriction and remained unchanged with time awake in both conditions of our study of the blood transcriptome.…”
Section: Effects Of Insufficient Sleep On the Circadian Modulation Ofmentioning
confidence: 99%